Hypothalamo-pituitary surveillance imaging in hypopituitary patients receiving long-term GH replacement therapy. - Frajese, G; Drake, WM; Loureiro, R; Evanson, J; Coyte, D; Wood, D; Grossman, AB; Besser, G; Monson, J (2001)
Most cases of adult-onset (AO) GH deficiency (GHD) result from the presence of hypothalamo-pituitary tumors or their treatment. GH replacement is now widely used in adults with hypopituitarism, but its effect on hypothalamo-pituitary tumor growth or recurrence is unknown. Anecdotal evidence from early experience of GH replacement in adults documented occasional tumor recurrence, but any relationship of this to the use of GH was unclear. We have now prospectively imaged the pituitary glands of 100 consecutive patients (60 females, 40 males; mean age, 46 yr; range, 18-69 yr) who had AO-GHD after appropriate treatment for a pituitary or peripituitary tumor. External radiotherapy had been given to 91 patients. All patients were treated with a dose titration regimen to maintain serum IGF-I between the median and upper end of the age-related reference range. Pituitary imaging was performed before the commencement of GH and after 6 and 12 months of treatment in all patients, again at 2 yr in 92 patients, at 3 yr in 63 patients, and after 4 yr in 23 patients. In only one patient was there evidence of slight intrasellar tissue enlargement at 6 months; GH replacement was continued, and there was no further change between 6 and 12 months. In all other patients, either the appearances were unchanged or the amount of tissue was reduced during long-term follow-up on GH. We have shown that hypothalamo-pituitary tumor recurrence was thus very rare over this time period in this group of GH-treated patients, and this is reassuring. Similar prospective longitudinal observation of patients who have not received postoperative irradiation and comparison with rates of tumor recurrence in control series are desirable.